Universal broadening of the Bardeen-Cooper-Schrieffer coherence peak of disordered superconducting films - Feigel'man, M V; Skvortsov, M A (Physical review letters, 2012)
In disordered superconductors, the local pairing field fluctuates in space, leading to the smearing of the BCS peak in the density of states and the appearance of the subgap tail states. We analyze the universal mesoscopic contributions to these effects and show that they are enhanced by the Coulomb repulsion. In the vicinity of the quantum critical point, where superconductivity is suppressed by the "fermionic mechanism," strong smearing of the peak due to mesoscopic fluctuations is predicted.